Factors Affecting Customer Loyalty in Siloam Hospitals Kebon Jeruk and Lippo Village - Franzeska Olivia Indra Putri; Chintya Nur; Margaretha Pink Berlianto (Jurnal Sains Pemasaran Indonesia (Indonesian Journal of Marketing Science), 2022)
The purpose of this study was to determine the effect of service quality, customer trust, and customer value on customer loyalty at the JCI standardized Siloam Hospital. Data collection in this study was conducted using an online questionnaire to 166 people who had visited Siloam Hospitals Kebon Jeruk and Lippo Village using simple random sampling method. Analysis using partial lease square-structural equation modeling (pls-sem) was carried out using the SmartPLS program to analyse the data. The findings from the study are that all the variables, which are service quality (interaction quality, physical environment quality, outcome quality), customer value and customer trust, have a positive relationship to customer loyalty at Siloam Hospitals Kebon Jeruk and Lippo Village.